2010
DOI: 10.1007/s00424-010-0788-2
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential channelopathies

Abstract: In the past years, several hereditary diseases caused by defects in transient receptor potential channels (TRP) genes have been described. This review summarizes our current knowledge about TRP channelopathies and their possible pathomechanisms. Based on available genetic indications, we will also describe several putative pathological conditions in which (mal)function of TRP channels could be anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 178 publications
(189 reference statements)
1
139
0
1
Order By: Relevance
“…Due to activation in response to a broad range of stimuli, including chemical compounds, temperature, mechanical inputs, etc., TRP channels are viewed as essential components in virtually all cellular responses to dynamic environmental changes (1,2). TRP channel dysfunction has been recently linked to a number of hereditary diseases in humans ranging from skeletal dysplasias, neuropathies, and electrolyte imbalance (magnesemia and hypocalcemia) to polycystic kidney disease (3)(4)(5)(6)(7).…”
Section: ؉mentioning
confidence: 99%
“…Due to activation in response to a broad range of stimuli, including chemical compounds, temperature, mechanical inputs, etc., TRP channels are viewed as essential components in virtually all cellular responses to dynamic environmental changes (1,2). TRP channel dysfunction has been recently linked to a number of hereditary diseases in humans ranging from skeletal dysplasias, neuropathies, and electrolyte imbalance (magnesemia and hypocalcemia) to polycystic kidney disease (3)(4)(5)(6)(7).…”
Section: ؉mentioning
confidence: 99%
“…Recent studies demonstrated that mis-sense mutations result in either constitutively-active or constitutively-inactive TRPV4 channels, [3][4][5][6][7] which leads to inheritable genetic disorders. To make it more complicated, point mutations at the same position generates different mutant TRPV4 channels that not only exhibit different electrophysiological properties in vitro but also reveals different level of surface expression.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-eight members of the TRP channel superfamily have been identified in almost every tissue of mammals [20]. Based on their amino acid sequence homology, mammalian TRP channels can be divided into six subfamilies, including TRP canonical (TRPC; TRPC1-7), TRP vanilloid (TRPV; TRPV1-6), TRP melastatin (TRPM; TRPM1-8), TRP mucolipin (TRPML; TRPML1-3), TRP ankyrin (TRPA; TRPA1) and TRP polycystin (TRPP; TRPP2, TRPP3, TRPP5) [20].…”
Section: Distribution and Functions Of Trp Channelsmentioning
confidence: 99%
“…Twenty-eight members of the TRP channel superfamily have been identified in almost every tissue of mammals [20]. Based on their amino acid sequence homology, mammalian TRP channels can be divided into six subfamilies, including TRP canonical (TRPC; TRPC1-7), TRP vanilloid (TRPV; TRPV1-6), TRP melastatin (TRPM; TRPM1-8), TRP mucolipin (TRPML; TRPML1-3), TRP ankyrin (TRPA; TRPA1) and TRP polycystin (TRPP; TRPP2, TRPP3, TRPP5) [20]. In general, all seven members of TRPC [2125]; TRPV1, -2, -4 [2628]; all TRPM, except TRPM5 [27] and TRPP1 and -2 [29,30], have been reported to expressed in vascular endothelial cells (ECs) from various sources.…”
Section: Distribution and Functions Of Trp Channelsmentioning
confidence: 99%